Eight new species of Polystichum (subg. Haplopolystichum; Dryopteridaceae) from limestone caves in Guangdong and Yunnan, China, with reference to species diversity in the karst terrains at high elevations in subtropical areas - Han, Meng-Qi; Liu, Yan; Zhang, Li-Bing (Phytotaxa, 2018)
Eight new fern species of Polystichum subg. Haplopolystichum (Dryopteridaceae) are described and illustrated from Guangdong and Yunnan provinces, southern and southwestern China, respectively. These eight species include P. deltatum, P. gejiuense, P. malipoense, P. oblongipinnarum, P. pingbianense, P. rectum, and P. superum from Yunnan, and P. hanmengqii from Guangdong. Four of the eight species are described from high elevations (around 2000 m) demonstrating that the limestone areas at high elevations in subtropical areas are species-rich and deserve special conservation attention. All eight species are so far known only from single caves; they are all classified as Critically Endangered (CR) following IUCN Red List criteria.